PERAN PATROLI KENDARAAN BERMOTOR RODA DUA DALAM MENCEGAH PENCURIAN DENGAN PEMBERATAN - Vavin, Alvan Fauzan (Advances in Police Science Research Journal, 2020)
ABSTRACT This research is motivated by the high number of Curat crime in the Garut police area, especially in the last 3 years. Curat is a type of C3 crime that has the highest number compared to other crimes. This caused disturbance to the public and therefore needed prevention efforts from the police to anticipate the incident. One of his efforts was to intensify the activities of two-wheeled patrols by Satsabhara. But apparently the role of patrol in its implementation has not been maximized. The research in this thesis is to find out how the implementation of Satsabhara's two-wheeled motor vehicle patrols in order to prevent Curat in the Garut Police jurisdiction, the factors that influence the implementation of the two-wheeled patrol Satsabhara Garut Police Station and the efforts made by Satsabhara's two-wheeled patrol to maximize the implementation of the patrol. In the conceptual literature the writer uses theories and concepts to analyze the above problems. The concepts and theories are: Curat concept, Sabhara concept, Patrol concept, role theory, and management theory. In this study a qualitative approach is used with the Field Research Method (Field Research) and uses triangulation of data, sources, and theoretical to obtain data validity. From the results of the study, it can be concluded that the implementation of two-wheeled patrol activities has been carried out with systematic management but still needs to be maximized. There are several factors that influence the role of two-wheeled patrols, namely internally and externally which can be strengths, weaknesses, opportunities and threats for the implementation of patrols. The recommendations of this study are (1) installing surveillance cameras in crime-prone areas, (2) increasing the number of patrol personnel, (3) rejuvenating Sarpras, utilizing drones and GPS (Global Positioning System), and (4) improving integration between functions especially Sector Police and line agencies. Keywords: Role, Patrol, Two Wheels, Motorized Vehicles, Satsabhara, Curat, Prevention.